Synthesis of Gold Nanoparticles Stabilized in Dextran Solution by Gamma Co-60 Ray Irradiation and Preparation of Gold Nanoparticles/Dextran Powder - Phan Ha Nu Diem; Doan Thi Thu Thao; Dang Van Phu; Nguyen Ngoc Duy; Hoang Thi Dong Quy; Tran Thai Hoa; Nguyen Quoc Hien (Journal of Chemistry)
Gold nanoparticles (AuNPs) in spherical shape with diameter of 6–35 nm stabilized by dextran were synthesized by γ-irradiation method. The AuNPs were characterized by UV-Vis spectroscopy and transmission electron microscopy. The influence of pH, Au3+ concentration, and dextran concentration on the size of AuNPs was investigated. Results indicated that the smallest AuNPs size (6 nm) and the largest AuNPs size (35 nm) were obtained for pH of 1 mM Au3+/1% dextran solution of 5.5 and 7.5, respectively. The smaller Au3+ concentration favored smaller size and conversely the smaller dextran concentration favored bigger size of AuNPs. AuNPs powders were prepared by spay drying, coagulation, and centrifugation and their sizes were also evaluated. The purity of prepared AuNPs powders was also examined by energy dispersive X-ray (EDX) analysis. Thus, the as-prepared AuNPs stabilized by biocompatible dextran in solution and/or in powder form can be potentially applied in biomedicine and pharmaceutics.